The adolescent : development, relationships, and culture - Rice, F. Philip; Dolgin, Kim Gale. (Boston, MA : Allyn & Bacon, 2005)
Dealing with adolescent psychology, this book offers an eclectic, interdisciplinary approach to the study of adolescence. Presenting both psychological and sociological viewpoints, it includes educational, demographic, and economic data. It also takes into consideration topics, such as ethnic identity formation, gender issues, and the Internet.
Includes bibliographical references and index.
Keywords: Teenagers -- Social conditions -- United States; Adolescent psychology -- United States; Adolescence